Cost Effectiveness Kombinasi Antihipertensi Candesartan-Bisoprolol dan Candesartan-Amlodipin Pada Pasien Rawat Jalan Penderita Hipertensi - Eny Nurhikma; Randa Wulaisfan; Musdalipah Musdalipah (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2019)
Today, in various countries, especially in Indonesia, the cost of health services is increasing. Hypertension is a degenerative disease that requires health costs for a long time. Increasing costs due to increasing chronic diseases threaten access and quality of health services, by which it is necessary to find a solution to overcome the problem of health financing. One method used is to analyze the guidelines for hypertension therapy and drug classes in the pharmacoeconomic aspects, namely Cost Effectiveness Analysis. This study aims to analyze the effectiveness of antihypertensive combination therapy in hypertensive patients at Bhayangkara Hospital, Kendari in 2019. The research method is descriptive with cross sectional study design. The analysis conducted is the cost effectiveness analysis (CEA) performed by calculating direct medical costs, the effectiveness of therapy based on blood pressure that reaches the target and calculating the value of ACER (Average Cost Effectiveness Ratio) and ICER (Incremenal Cost Effectiveness Ratio). Data were collected prospectively which fulfilled the inclusion and exclusion criteria. The results showed the therapeutic effectiveness and the value of ACER obtained from 31 hypertensive patients were a combination of Candesartan – Bisoprolol that was ACER value of 85.71% (2,314), and combination of Candesartan – Amlodipin of 70.58% (2,643). ICER value of 7,832 indicates that the price of drugs is more expensive but more effective therapy.